Species composition and distribution of microalgae in the Sukhodol River estuary (Ussury Bay, Peter the Great Bay) in autumn. 1. Phytoplankton - Nikolay V. Kolpakov; Andrey A. Begun (Известия ТИНРО, 2014)
Species composition and quantitative distribution of phytoplankton in the Sukhodol River estuary were studied in September of 2012. It total, 48 species of diatoms are registered, mostly belonged to microphytobenthos (63 %). The most numerous are mesohaline species and species indifferent to salinity (in sum 69 %). The number of diatoms varied from 5.4 ˑ 103 to 866.2 ˑ 103 cells/l (on average 138.4 ˑ 103 ± 75.9 ˑ 103 cells/l), their biomass varied from 5.0 to 816.8 mg/m3 (on average 199.5 ± 71.0 mg/m3: 467.8 mg/m3 in the external estuary, 285.4 ± 117.5 mg/m3 in the deep-water part of the internal estuary, and 42.0 ± 16.5 mg/m3 on the shallows of the internal estuary). Species composition of phytoplankton is determined by water structure: Dactyliosolen fragilissimus (74 % of biomass) , Skeletonema costatum (15 %) and Coscinodiscus oculus iridis (8 %) are the most abundant in the external estuary where brackish water spreads in the upper layer and salt water occupies the bottom layer; Ulnaria ulna (72 %), Melosira varians (12 %) and Ctenophora pulchella (4 %) are the most abundant in the deep-water part of the internal estuary with almost fresh water in the upper layer and brackish water at the bottom; and Achnanthes lanceolata (22 %), S. costatum (21 %), Rhopalodia musculus (14 %), Pinnularia gibba (6 %), and C. pulchella (5 %) dominate on the shallows of internal estuary with only one water layer occupied by fresh water. Domination of D. fragilissimus and S. costatum indicates a high level of eutrophication in the Sukhodol estuary that presumably is caused by terrigenous biogenic elements supply. The biogenic elements recycled and accumulated in the bottom sediments are dispersed in the estuarine waters by tidal and wind-driven turbulence.